SIMULATION OF THE MULTI-OBJECTIVE RESOLUTION OF AIRCRAFT CONFLICT - Kharchenko, Volodymyr; Vasyliev, Denys; Bo, Wang (Proceedings of National Aviation University (archive), 2015)
The article represents computer simulation of aircraft conflict resolution using the method of multi-objective sequential synthesis of conflict-free space-time trajectories. The results of computer simulation show that the method provides the conflict resolution according to flight regularity, efficiency and maneuvers complexity criteria.